High-Entropy Electrode Materials: Synthesis, Properties and Outlook - Li, Dongxiao; Liu, Chang; Tao, Shusheng; Cai, Jieming; Zhong, Biao; Li, Jie; Deng, Wentao; Hou, Hongshuai; Zou, Guoqiang; Ji, Xiaobo (Nano-Micro Letters, 2024)
High-entropy materials represent a new category of high-performance materials, first proposed in 2004 and extensively investigated by researchers over the past two decades. The definition of high-entropy materials has continuously evolved. In the last ten years, the discovery of an increasing number of high-entropy materials has led to significant advancements in their utilization in energy storage, electrocatalysis, and related domains, accompanied by a rise in techniques for fabricating high-entropy electrode materials. Recently, the research emphasis has shifted from solely improving the performance of high-entropy materials toward exploring their reaction mechanisms and adopting cleaner preparation approaches. However, the current definition of high-entropy materials remains relatively vague, and the preparation method of high-entropy materials is based on the preparation method of single metal/low- or medium-entropy materials. It should be noted that not all methods applicable to single metal/low- or medium-entropy materials can be directly applied to high-entropy materials. In this review, the definition and development of high-entropy materials are briefly reviewed. Subsequently, the classification of high-entropy electrode materials is presented, followed by a discussion of their applications in energy storage and catalysis from the perspective of synthesis methods. Finally, an evaluation of the advantages and disadvantages of various synthesis methods in the production process of different high-entropy materials is provided, along with a proposal for potential future development directions for high-entropy materials. Highlights: 1 The developmental history of high-entropy materials and the conceptual origin of “high entropy” is comprehensively reviewed. 2 The preparation methods of various high-entropy electrode materials are comprehensively reviewed. 3 The application properties of various high-entropy electrode materials in electrocatalysis and energy storage are comprehensively reviewed, with a prospective outlook on the future development of such materials.